Indoor Air Temperature and Agitation of Nursing Home Residents With Dementia. (August 2017) - Tartarini, Federico; Cooper, Paul; Fleming, Richard; Batterham, Marijka
This study aimed to determine the specific correlation between indoor air temperature and agitation of nursing home residents with dementia. Agitated behaviors of 21 residents, living in 1 nursing home, were assessed for a 10-month period using the Cohen-Mansfield Agitation Inventory (CMAI). The CMAI Total Frequency scores were found to increase significantly when indoor average temperatures deviated from 22.6°C. In addition, cumulative exposure to temperatures higher than 26°C and lower than 20°C was linearly correlated with CMAI Total Frequency scores. Results showed that agitated behaviors not only affected the person manifesting them but were found to be disruptive for other residents and the delivery of care. Agitation can, therefore, be potentially reduced by limiting the range of indoor air temperature variations, and aged care providers should ensure that a thermally comfortable environment is provided in nursing homes to enhance comfort and well-being of all occupants.